DECLIVITY OF LAND AND POTENTIAL FOR AGRICULTURAL MECHANIZATION OF THE HYDROGRAPHIC BASIN OF PEDERNEIRAS STREAM - PEDERNEIRAS/SP - Garcia, Y. M.; Campos, S.; Tagliarini, F. S. N.; Campos, M.; Rodrigues, B. T. (Revista Brasileira de Engenharia de Biossistemas, 2020)
The steepness of the land contributes to the runoff of the water, because the greater the stretch on the slope, the greater the runoff of water through the surface, dragging other materials to the surface water resources, influencing the water quality and the infiltration and erosion processes fluvial and pluvial, as well as in the type of vegetation, as well as contributing to _________________ seca@fca.unesp.br the formation of the soil and serving as an indicator in the definition of areas of risk and use restriction. The steepness of the rivers can be associated with the flow speed, sediment transport and conformation of the permanent preservation areas. This work aimed to analyze the slope of the land in the hydrographic basin of the Pederneiras stream, in the state of São Paulo and classify it according to the areas suitable and unfit for agricultural mechanization. The study area is located between the geographical coordinates 22 ° 20 ’and 22 ° 26’ of latitude S and 48° 44’ and 48° 56’ of longitude W Gr., located in the municipalities of Agudos and Pederneiras, state of São Paulo, with an area of ​​14918.28 ha. The slope maps were elaborated using geoprocessing techniques, having as cartographic base: the planialtimetric charts of the Brazilian Institute of Geography and Statistics and the image of the Sentinel-2 satellite in a Geographic Information System environment - ArcGis 10.4.1. The classes of slope of the soil were classified as flat relief (0 - 3%), smooth wavy (3 - 8%), wavy (8 - 20%), strong wavy (20 - 45%), mountainous (45 - 75%) and steep (> 75%) and areas for agricultural mechanization as suitable (mechanizable areas) and unfit (non-mechanized areas). The results showed that the flat and gently wavy relief predominated in almost 89% of the area, framing them in areas suitable for mechanization with small restrictions.